2014
DOI: 10.2105/ajph.2013.301563
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Policies and Practices in US State Prison Systems

Abstract: Medicaid is an important source of health care coverage for prison-involved populations. From 2011 to 2012, we surveyed state prison system (SPS) policies affecting Medicaid enrollment during incarceration and upon release; 42 of 50 SPSs participated. Upon incarceration, Medicaid benefits were suspended in 9 (21.4%) SPSs and terminated in 28 (66.7%); 27 (64.3%) SPSs screened prisoners for potential Medicaid eligibility. Although many states supported Medicaid enrollment upon release, several did not. We have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…27,28 David Rosen and coauthors found that most states with suspension policies reported being able to reactivate benefits within a month of release but that some states with the policies reported that reenrollment was not an automatic process. 28 Furthermore, Joseph Morrissey and coauthors concluded that some local jurisdictions suspend benefits, despite state policies that require termination of benefits. 16 Future research should characterize states’ suspension activities to understand the effects on enrollment after release and identify best practices for the implementation of suspension policies.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 David Rosen and coauthors found that most states with suspension policies reported being able to reactivate benefits within a month of release but that some states with the policies reported that reenrollment was not an automatic process. 28 Furthermore, Joseph Morrissey and coauthors concluded that some local jurisdictions suspend benefits, despite state policies that require termination of benefits. 16 Future research should characterize states’ suspension activities to understand the effects on enrollment after release and identify best practices for the implementation of suspension policies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, providing sensitivity training for health care providers working with this population may be useful. Nationally, about one third of prisons do not provide Medicaid enrollment support prior to release (Rosen et al, 2014). Providing HIV-infected inmates with support to enroll in Medicaid (Teitelbaum & Hoffman, 2013) before release would facilitate continuity of care after release, as well as provide individuals with the ability to find providers who meet their needs.…”
Section: Discussionmentioning
confidence: 99%
“…The ACA offers a number of provisions that will expand access to the health care insurance market for individuals living with HIV, such as the expansion of Medicaid coverage and open enrollment in the health insurance exchanges (Crowley & Kates, 2012). Researchers have also predicted that broader eligibility for Medicaid will not only improve health care access for HIV-infected inmates after release but also reduce state health care spending (Rosen et al, 2014). The ACA can also expand essential services under Medicaid, including prescription drugs, and mental health and substance use services, which have important implications for formerly incarcerated populations who disproportionately suffer from mental and behavioral health problems (Crowley & Kates, 2012).…”
Section: Discussionmentioning
confidence: 99%